Associations of History of Displacement, Food Insecurity, and Stress With Maternal-Fetal Health in a Conflict Zone: A Case Study - González-Fernández, Doris; Sahajpal, Revathi; Chagüendo, José E.; Ortiz Martínez, Roberth A.; Herrera, Julián A.; Scott, Marilyn E.; Koski, Kristine G. (Frontiers in Public Health, 2020)
Background : In populations with a history of conflict, early identification of pregnant women who are at risk of adverse pregnancy outcomes is challenging. We investigated if food security and diet quality, clinical biomarkers, and stress were associated with 3 indicators of maternal-fetal wellbeing: 1) symphysis-fundal height (SFH), 2) sonography-estimated fetal weight, and 3) sonography-calculated amniotic fluid index (AFI). Methods: For this cross-sectional study, 61 women with high-risk pregnancies were recruited after referral to the obstetrics and gynecology unit at San José Hospital in Popayán, Colombia. Multiple stepwise linear and ordered logistic regression were used to identify associations between SFH, sonography-estimated fetal weight and AFI classification with questionnaire-obtained history of displacement, food insecurity and both a specific conflict-related stress questionnaire and the Colombian biopsychosocial risk assessment . Results: History of displacement emerged as a determinant of lower SFH Z scores. Severity of anxiety-like symptoms and lacking interest in daily activities were associated with a higher AFI. In contrast family support, element of the Colombian biopsychosocial risk assessment, reduced the odds of a higher AFI and was associated with higher sonography-estimated fetal weight. Moreover, higher hemoglobin concentrations, taking iron supplements and a higher diastolic blood pressure were positively associated with larger SFH Z scores, but taking aspirin for underlying hypertensive disorders of pregnancy and sleeping > 8 hrs/day were associated with lower sonography-estimated fetal weight. Conclusion: Maternal-fetal health indicators, SFH, sonography-estimated fetal weight and AFI were able to capture overlooked risk factors associated with maternal-fetal well-being that differed from those for sonography estimated fetal weight. Associations of stress indicators with maternal-fetal biomarkers highlight the need of a systematic assessment of stress in pregnant women from conflict zones.